Treatment outcomes of rifampin-sparing treatment in patients with pulmonary tuberculosis with rifampin-mono-resistance or rifampin adverse events: A retrospective cohort analysis. (October 2017) - Park, Shinhee; Jo, Kyung-Wook; Lee, Sang Do; Kim, Woo Sung; Shim, Tae Sun
Abstract: Background: Rifampin (RIF) mono-resistant tuberculosis (RMR-TB) is a rare disease. Current guidelines recommend that RMR-TB be treated as multidrug-resistant TB (MDR-TB) but the evidence is scarce. Methods: We conducted a retrospective cohort study on pulmonary TB patients to investigate the characteristics and outcomes of RMR-TB. The characteristics of RMR-TB were compared with those with adverse events to rifampin (RAE-TB). Results: Forty-four RMR-TB and 29 RAE-TB patients were enrolled. RMR-TB patients showed more alcohol use, prior history of TB, and radiologically severe disease, while RAE-TB patients were older and had more comorbidities and combined extrapulmonary TB. A fluoroquinolone (FQ) was the drug most commonly added (70.5%, RMR-TB; 82.8%, RAE-TB). Median treatment duration was 453 days in RMR-TB and 371 days in RAE-TB (p = 0.001) and treatment success rates were 87.2% (34/39) and 80.0% (20/25), respectively (p = 0.586). Subanalysis of the RMR-TB group by treatment regimen (standard regimen [n = 11], standard regimen + FQ [n = 12], MDR-TB regimen [n = 21]) revealed a higher rate of radiologically severe disease in the MDR-TB subgroup, with similar treatment success rates for the subgroups (85.7% [6/7]), 91.7% [11/12], and 85.0% [17/20], respectively) despite different durations of treatment (345, 405, and 528 days, respectively). Two recurrences (33.3% [2/6]) developed only in standard regimen subgroup, suggesting that standard regimen is not enough to treat RMR-TB patients. Conclusions: The treatment outcome of RMR-TB with 1 st -line drugs + FQ was comparable to that of MDR-TB regimen. Shorter treatment duration may be considered for RMR-TB patients compared with MDR-TB patients. Highlights: Outcomes of rifampin-sparing treatment were analyzed in patients with RMR-TB. Outcomes were similar between 1 st -line drug + FQ and MDR-TB regimen subgroup. Shorter than 20 months of treatment duration may be considered for patients with RMR-TB. The standard regimen for drug-susceptible TB was associated with worse outcomes in RMR-TB patients.